112k views
3 votes
Perform the indicated operation. (4 - 8i)(2 – 5i)​

User Akotian
by
4.3k points

2 Answers

4 votes

Answer:

-32 - 36i.

Explanation:

(4 - 8i)(2 – 5i)

= 4*2 + 4*-5i + 2*-8i + (-8i*-5i)

= 8 - 20i - 16i + 40i^2 Now i^2 = -1 so:

= 8 - 36i - 40

= -32 - 36i.

User Gabriel Cartier
by
5.3k points
1 vote

Hi there! :)

Answer:


\huge\boxed{-32 - 36i}

(4 - 8i) (2 - 5i)

FOIL:

(4 · 2) + (4 · (-5i) + ((-8i) · 2) + ((-8i) · (-5i)) =

Simplify: (Remember, i² = -1:

8 + ( - 20i) + (-16i) + (40i²) =

8 - 20i - 16i - 40

Combine like terms:

-32 - 36i

User Naliba
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.